Sustainable Welfare Model for the Internally Displaced Persons (IDPs) in the North-Eastern Nigeria: The Role of Waqf Financing - Muhammad Abubakar, Adam (IKONOMIKA, 2021)
The North East region of Nigeria has been experiencing the devastating impact of Boko Haram insurgency which triggered humanitarian crisis and destruction of infrastructure, leading to many becoming internally displaced persons in their country. The Federal Government and the Northeast State Governments, alongside the local and international Non-governmental organizations and development partners have been mostly providing relief services and materials to the IDPs, but despite all these efforts, there is still a funding gap, thus the need to bridge this vacuum; to supplement the efforts of governmental and non-governmental organizations in providing a long term and sustainable welfare model. It is against this backdrop that this study aims at unlocking the potentials of waqf financing model in catering for short-term and long-term welfare of IDPs in the Northeast and how the model could be properly utilized to complement the efforts of governmental and non-governmental organizations in the region. Multistage sampling method was employed in selecting respondents for the study. In the first stage, three States were purposively selected out of the six States of the region based on the devastation level by the insurgency. Thematic Analysis was employed as the method of data analysis. Both descriptive and inferential statistics were used to summarize and interpret the results of the thematic analyses of the data obtained. The findings of this research have shown the potentials of Waqf financing in bridging the funding gap of IDPs welfare in the north-east. The study also found out that food and clothing are the most critical areas that require immediate attention in the Waqf based IDPs welfare and that, the Investment Waqf Model will be the best means of financing the IDPs Welfare programme in the Northeast due to its modest unique potential advantages over other models. Finally, the study also identified that Conversion of IDPs Support Waqf to Less privilege Support Waqf in case of return of IDPs to their respective communities is the best exit plan for Waqf based IDPs welfare model amongst all other listed exit plans. Key Words: North-East, IDPs, Welfare and Waqf Financing